2019
DOI: 10.1111/jce.14322
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of patients undergoing conventional vs leadless pacemaker implantation: A multicenter observational study

Abstract: Background: Leadless pacemakers (L-PM) are an emerging effective and safe technology that offer an alternative to conventional pacemakers (C-PM) for right ventricular stimulation. However, there is little information about their potential benefits for quality of life (QoL) in patients with L-PM. We compared QoL between patients with L-PM and C-PM. Methods:The study population comprised patients undergoing single chamber pacemaker implantation from December 2016 to March 2018. The SF-36 questionnaire was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Besides, previous studies showed that leadless pacing is associated with better quality of life than conventional pacing in both physical and mental health 10 . However, To date, there are no randomized controlled trials that compare efficacy and long‐term safety between transvenous and leadless pacemakers and further studies comparing both systems are needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, previous studies showed that leadless pacing is associated with better quality of life than conventional pacing in both physical and mental health 10 . However, To date, there are no randomized controlled trials that compare efficacy and long‐term safety between transvenous and leadless pacemakers and further studies comparing both systems are needed.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 In addition, it is also demonstrated that LPs are associated with better quality of life than TV-PPM. 10 At the end of battery life, a reasonable strategy might be to implant another LP without extracting the old one. There are concerns regard battery longevity specially with the paucity of data on device extraction and the number of concomitant LPs that can be implanted safely.…”
Section: F I G U R E 1 2021 Esc Guidelines On Cardiac Pacing and Card...mentioning
confidence: 99%
See 1 more Smart Citation
“…Even for complication-free transvenous pacemaker implants, it can be distressing for the patient to have a subcutaneous bulge, reminding them of their dependence on a pacemaker. Contrastingly, patients with LPs have been shown to have superior physical function, mental health, and significantly lower pacemaker-related discomfort [ 9 ]. Indications for leadless pacing include atrioventricular (AV) block with atrial fibrillation, bradycardia, and AV block or sinus node disease that does not require frequent ventricular pacing [ 1 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the use of leadless pacemakers may be associated with a lower complication rate compared to conventional transvenous pacemakers 6,7 . The implantation procedure of leadless pacemakers is simpler and less invasive compared to conventional transvenous pacemakers, leading to a better quality of life 8 . However, the risk of cardiac tamponade has been reported more with leadless pacemaker use than that with conventional transvenous pacemaker use 9 .…”
Section: Introductionmentioning
confidence: 99%